Comparison of outcomes in patients with or without ARC‐HBR criteria undergoing PCI with polymer‐free biolimus coated stents: The BioFreedom France study. Issue 1 (15th November 2022) - Garot, Philippe; Brunel, Philippe; Dibie, Alain; Morelle, Jean‐François; Abdellaoui, Mohamed; Levy, Raphy; Carrié, Didier; Karsenty, Bernard; Robin, Christophe; Berland, Jacques; Copt, Samuel; Sadozai Slama, Sara; et al.
Abstract: Background: The polymer‐free biolimus coated stent (BioFreedom) was shown to be superior to bare metal stents in the LEADERS FREE randomized trial in high bleeding risk (HBR) patients treated with 1‐month dual antiplatelet therapy (DAPT). However, there is limited outcome data with this device in an all‐comers' population. Methods: We conducted a prospective single‐arm study of patients undergoing percutaneous coronary intervention with the polymer‐free biolimus coated stent in 25 centers in France with wide inclusion criteria including multivessel disease, complex lesions, and acute coronary syndromes. The primary endpoint was the incidence of target lesion failure (TLF), a composite of cardiac death or target‐vessel myocardial infarction (MI) or clinically indicated target lesion revascularization (ci‐TLR) at 1‐year. The patient population was classified according to the presence (or not) of HBR criteria according to the recent ARC‐HBR definition. Results: Between April 2019 and April 2020, 1497 patients were enrolled. TLF occurred in 101 (6.9%) patients, including cardiac death in 35 (2.4%), target vessel MI in 20 (1.4%) and ci‐TLR in 65 (4.5%) of them. There were 491 HBR patients (32.8%) and 1006 non‐HBR patients. The median duration of DAPT was 74 days in the HBR group versus 348 days in the non‐HBR group ( p  < 0.0001). TLF occurred in 44 (9.2%) of the HBR group and in 57 (5.8%) of the non‐HBR group (relative risk 1.62 [95% confidence interval: 1.10–2.41], p  = 0015). Compared to the non‐HBR group, HBR patients had higher rates of cardiac death (4.4% vs. 1.4%, p  = 0.0005) and target vessel MI (2.9% vs. 0.6%, p  = 0.0003), but similar rates of ci‐TLR. BARC 3–5 bleeding occurred in 6.2% of the HBR group versus 1.4% of the non‐HBR group ( p  < 0.0001). Conclusion: In this multicenter all‐comers study, HBR patients treated with a polymer‐free biolimus coated stent had, compared to non‐HBR patients, an increased risk of cardiac death and MI, and despite a shorter duration of DAPT, continued to have higher rates of BARC 3–5 bleeding.